Models of the Universe: ontological and physical problems - Vladlenova, Iliana; Kalnytskyi, Eduard (International Society of Philosophy and Cosmology (ISPC), 2022)
The primary target of this paper is a philosophical analysis of modern models of the universe in cosmology. Understanding the existence of being is directly related to understanding both the world and oneself. An important characteristic of ontology is time, matter, space which forms the ontological horizon of presence. Ontology tries to describe the fundamental principles of our universe in a comprehensive and consistent way, but the more the system includes different levels and objects, the more difficult it is to make an ontological description, especially when it comes to the structure of the universe. Cosmology historically develops in the bosom of ontological discourse, as it tries to describe the fundamental structure, nature, and dynamics of the universe. In this paper, we identify the concept of the Bipolar Universe. According to this model, two mirror-symmetric parallel universes were formed during the Big Bang. Within the framework of this concept, the problem of baryogenesis is solved. It is possible to allow some interaction between two parallel universes, for example, the correlation of the motion of matter and solve the monopole problem. The article describes the hypothesis of the existence of mirror matter. The formation of ideas about the structure of our world articulates the ontological question of what reality is and what its metaphysical essence is. Three important ontological categories: time, space, and matter, form the ontological basis of the structure of our universe.
Keywords: ontology; reality structure; cosmology; bipolar universe; parallel worlds; baryogenesis